Uniaxial hysteretic spring models for static and dynamic analyses of self-centering rocking shallow foundations. (1st December 2022) - Lu, Yang; Xiong, Feng; Zhong, Jie
Abstract: Self-centering rocking shallow foundations have been proved to be a potential alternative to conventional foundations that provide superstructures with "fixed-base" constraints. Through appropriate design of foundations to undergo controlled rocking motions, they serve as "seismic fuses" (associated with a rocking isolation mechanism) which enable their supporting structures to remain even undamaged during intense shaking events without compromising the overall resilience of the soil–structure interaction (SSI) system. Recent progress in rocking shallow foundations has heightened the need for simple and efficient models in seismic design and evaluation of structures with rocking isolation. To this end, the paper proposes uniaxial hysteretic rocking spring models to enrich modeling of rocking-dominated foundation response in engineering practice. Two types of models are developed, including a bilinear hysteretic model (BHM) and a smooth hysteretic model (SHM). These models are defined by dimensionless backbone curves and recentering ratio based hysteretic rules obtained by performing monotonic and cyclic push-over analyses using a nonlinear hysteretic Winkler foundation (NHWF). The current implementation is based on square or strip footings on saturated clay foundations. Using the developed models, seismic performance of practical SSI systems consisting of rigid shear walls or deformable bridge piers on rocking shallow foundations are examined. Highlights: Uniaxial spring models developed for rocking shallow foundations. Dimensionless foundation moment–rotation backbone curve determined. Rotation amplitude and F sv dependent recentering ratios proposed. Smooth hysteretic model and bilinear hysteretic model compared. Seismic deformation demands of SDOF structures on rocking springs examined.